Jerat Hutang: Analisis Putusan Nomor 612/Pid.B/2023/PN Rhl Tentang Kejahatan terhadap Kemerdekaan Orang - Khoiri, Syahid Al; Pakpahan, Zainal Abidin; Toni, Toni (CV. Social Politic Genius (SIGn), 2024)
This research aims to analyze Decision Number 612/Pid.B/2023/PN Rhl concerning the crime of kidnapping as a crime against personal freedom motivated by debt issues. This normative legal research employs a statute approach and a case study. Data analysis uses a qualitative content analysis to describe the issues and answer the research objectives. The research results indicate that Decision Number 612/Pid.B/2023/PN Rhl explicitly criminalizes acts of deprivation of liberty committed to resolving debt problems. The Panel of Judges’ considerations highlight the psychological impact of trauma on the victim as an aggravating factor, while the Defendants’ remorse and attempts at reconciliation serve as mitigating factors. Nevertheless, this act of kidnapping remains an ordinary offence whose legal process cannot be overridden by agreements between the parties. The implications of this decision provide a comprehensive understanding of the boundaries that must not be violated in debt collection. Thus, Decision Number 612/Pid.B/2023/PN Rhl contributes to creating a just and equitable legal climate and provides guaranteed protection of human rights in the context of debt collection.